Upaya Meningkatkan Meningkatkan Kemampuan Komunikasi Matematis Siswa dengan Pembelajaran Two Stay Two Stray - Rosdiana Br. Siallagan (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2020)
This study aims to determine the increase in students' mathematical communication on the Cartesian coordinates of SMP Negeri 2 Tanjung Balai. This type of research is classroom action research with 20 research subjects. The instruments used were tests and observations. The results of observations of student activities during the learning process are 75.5% in the active category, the observation of the results of teacher activities during the learning process is 3.3 in the very good category, the achievement of individual student learning completeness with the correct answer report is at least moderate or 65%, the achievement of learning completeness Classically, there are 85% of students obtaining individual student learning completeness at least moderate or 65%, there is an increase in the average proportion of student communication communication in CYCLE I which is 58.65 and CYCLE II which is 76.565, it can be concluded that the Two Stay Two Stray learning model can improve students' mathematical communication on Cartesian coordinate material.